0.3-V Nanopower Biopotential Low-Pass Filter - Kulej, Tomasz; Khateb, Fabian; Kumngern, Montree (My University, 2020)
This paper presents a compact power-efficient CMOS fourth-order low-pass filter suitable for electrocardiogram (ECG) acquisition systems. The CMOS structure of the proposed filter utilize the bulk-driven technique and operates in subthreshold region to achieve extremely low-voltage supply (0.3V) and nanopower consumption (0.676 nW) for cut-off frequency of 100 Hz. The filter was designed and simulated using 0.18μm CMOS TSMC technology. The total input referred noise of the filter is 87μ Vrms and the dynamic range is 58.1 dB. The filter offers the best figure of merit of 2.91× 10-14 J, the lowest power consumption and voltage supply, compared with the previous state-of-the-art nanowatt filter designs.
Keywords: Biopotential filter; bulk-driven; low power; low voltage